Tuberous Sclerosis Complex in Chinese patients: Phenotypic analysis and mutational screening of TSC1/TSC2 genes. (October 2019) - Lin, Shan; Zeng, Jia-Bin; Zhao, Gui-Xian; Yang, Zhen-Zhen; Huang, Hui-Ping; Lin, Min-Ting; Wu, Zhi-Ying; Wang, Ning; Chen, Wan-Jin; Fang, Ling
Highlights: Analysis of the genotype-phenotype correlation of 77 Chinese TSC patient. Combining direct Sanger sequencing with Multiplex ligation-dependent probe amplification to screen mutations. Expanded spectrum of mutations with fourteen novel mutations. Abstract: Purpose: Tuberous sclerosis complex (TSC) is characterized by the development of hamartomas in multiple organ systems. This study attempted to screen mutations and to investigate the mutation distribution and related phenotypes including epilepsy of Chinese TSC patients. Methods: We performed the genotypic analysis of TSC1 and TSC2 genes in 77 unrelated Chinese TSC patients using direct Sanger sequencing and Multiplex ligation-dependent probe amplification (MLPA). Results: Mutations were identified in a total of 63 (81.8%) cases, including 18 TSC1 mutations (8 nonsense mutations, 6 frameshift, 1 in-frame shift, 1 missense and 2 splice-site) and 45 TSC2 mutations (13 missense, 3 nonsense, 6 splicing, 6 in-frame shift, 12 frameshift mutations and 5 large deletions). Large deletions were presented exclusively in TSC2 gene, accounting for 7.9% of all mutations in this study. Fourteen novel mutations were identified in this study. Conclusions: Epilepsy occurs in approximately 75.3% (58/77) of patients. Hypomelanotic macules occurred significantly more often in patients with TSC2 mutations and cases with TSC1/TSC2 mutations had a significantly higher frequency of cortical nodule than patients with no mutations identified. Overall, our data expands the spectrum of mutations associated with the TSC loci and will be of value to the genetic counseling in patients with the disease.